Examining the Correlation among Motivation, Self-efficacy, and English Language Proficiency (ELP) across Gender - Aprianto, Dedi; Agus Syahid; Abdussamad, Zainudin (Journal of Language and Literature Studies, 2024)
The motivational aspect has great influence on the urge to develop as does self-efficacy brings optimism towards attaining learning goals. High self-efficacy results to motivation for success in learning activities since the individual believes in his or her ability to accomplish a task. The current study indicates the importance of motivation and self-efficacy as the primary indicators of English learning proficiency. Therefore, the present study is aimed at assessing the correlation between motivation, self-efficacy, and language proficiency, with a particular focus on gender. The study employs a quantitative study by using a correlational method, using two types of questionnaires to obtain the data from the sample consisting of 71 participants, both 48 males and 23 females. The interplay of motivation, self-efficacy, and language proficiency across gender was statistically analyzed by using a Pearson correlation and a Multiple regression was used to explore the predictive ability of psychological variables. In male students, the correlation analysis found motivation demonstrated a strong correlation to self-efficacy of (R=0.680, p < 0.01) with a Sig.value (0.000 < 0.05), motivation with language proficiency also demonstrated a strong correlation (R=0.735, p < 0.01) with a Sig. value (0.000 < 0.05), and self-efficacy and language proficiency revealed a strong correlation (R=0.662, p < 0.01) with a Sig. value (0.000 < 0.05). In female students, motivation is closely-related to self-efficacy with a sig. value (0.000 < 0.05) and showed a very strong correlation (R=0.831, p < 0.01), while motivation and language proficiency resulted a strong correlation (R=0.748, p < 0.01) with a Sig. value (0.000 < 0.05), and self-efficacy is also correlated strongly with language proficiency (R=0.692, p < 0.01). The regression model for both genders demonstrated that motivation and self-efficacy significantly predict language proficiency; for male students, the adjusted (R2= 57.1% > 0.33 or < 0.67), while for female students, the adjusted (R2= 53.3% > 0.33 or < 0.67). The results reveal that moderate levels of motivation and self-efficacy must have been associated with language proficiency. Undoubtedly, motivation and self-efficacy are moderate indicators to predict language proficiency in ELT. The study can assist English and non-English teachers, students, etc. to increase motivation and self-efficacy theories, gender pedagogies and classroom learning climate and student language achievement.